Method of phase compensation and pattern transformation for array antennas with arbitrarily oriented circularly polarised elements - Zhongtian Jing; Yubing Han (IET Microwaves, Antennas & Propagation, 2023)
Abstract The inconsistent polarised directions and the radiation pattern transformation of the elements need to be considered in the analysis and simulation of large circularly polarised conformal arrays. Without relying on full‐wave simulations of the full array, a polarisation phase compensation and a pattern transformation method are proposed to solve these problems. When the position and orientation of the conformal array elements are known, the polarisation phase compensation method can provide a solution to keep the initial phase direction of each circularly polarised antenna element consistent in the global coordinate system. Then, a pattern transformation method is proposed to obtain the radiation pattern of each antenna in the global coordinate system. In this method, the local antenna polarised radiation patterns with amplitude and phase information are expressed in the global coordinate system through the mutual conversion relationship between the local and global coordinate systems. These methods can provide a guidance for array design and performance simulation, especially theoretically applicable to the arbitrary conformal arrays.